(untitled) - Yamamoto, Shichihei (New York, 1992)
The theoretical path to the development of capitalism is fundamentally based around the method of profit accumulation; i.e. the process of turning M into M’. In each method, capital increases its influence as a social relation, and it is when the three methods fuse together that capital becomes the dominant social relation, and hence when capitalism appears fully-developed.
Keywords: Capitalism,Chủ nghĩa tư bản; Japan,Nhật Bản